Hazor rulership and ritual manipulation. (2nd April 2020) - Susnow, Matthew; Bechar, Shlomit; Yasur-Landau, Assaf
ABSTRACT: Hazor was unquestionably the largest Bronze Age Canaanite site, standing as an anomaly in the southern Levant in terms of its size, elaborate public architecture, special geopolitical stature and far-reaching international networks. While the site has been well established as an urban center with many temples, the use of each of Hazor's temples and how they relate to one another remains unclear. In this study, we analyze the rituals and other activities that were conducted within Hazor's numerous temples. The methodology we employ stresses, fundamentally, the necessity to contextualize objects within entire assemblages – through spatial analysis – to most accurately assess how Hazor's cultic spaces were actually used. We apply the same methodology to other MB and LB Canaanite temples to establish a generalized ideal-type temple assemblage for Canaanite temples. This study successfully demonstrates that Hazor's temples substantially diverge from the ideal temple assemblage, indicating cult at Hazor was practiced differently than elsewhere in the region. This includes the atypical distribution of certain cultic vessels (e.g. miniature vessels), the appearance of special vessels in ritual contexts (e.g. cups), and a fundamentally different use of indoor and outdoor spaces when compared to other Canaanite temples. It turns out that Hazor's elites were major factors controlling the anomalies of cultic practice at the site. Hazor's rulers impacted cultic architectural forms and locations and played instrumental roles in dictating and manipulating the types of rituals and associated cultic paraphernalia that were allowed to be performed and used throughout the entire settlement landscape.